Novos biomarcadores de função renal não convencionais em pacientes com hemoglobinúria paroxística noturna - Pro, Juan Daniel Zuñiga (2019)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare chronic acquired hemolytic disease, of which the pathophysiology of renal dysfunction is not well understood. Objectives:To evaluate the importance of new biomarkersof early renal injury in patients with PNH. Methods:A cross-sectional, observational and analytical case-control study was conducted with 17 PNH patients from the HUWC hematology outpatient clinic. After confirmation of the diagnosis by peripheral blood flowcytometry, random urine and blood samples were collected. Clinical and renal parameters associated with PNH were evaluated. For renal function analysis the glomerular filtration rate (eGFR) was estimated using the CKD-EPI formula. Two renal biomarkerswere evaluated: urinary KIM-1 (uKIM-1) and urinary MCP-1 (uMCP-1), which were quantified using the immunoassay method (ELISA). Statistical comparisons and correlations were performed to assess the role of renal biomarkers in detecting subclinical renal changes in PNH. Results:Patients with PNH had noticeablehematological disorders and signs of intravascular hemolytic anemia. The uMCP-1 levels were significantly higher compared to the control group (p = 0.017) and showed positive correlations with sodium excretion fraction (p = 0.004), chloride excretion fraction (p = 0.008),and inverse correlationwith uric acid (p = 0.016). Regarding uKIM-1 levels, no relevant statisticalsignificance wasfound between the two groups (p = 0.65). Conclusion:No clinically evident renal dysfunction was observed using the traditional markers of renal function. However, uMCP-1 showed elevated levels in PNH patients, who may have renal damage to the proximal tubule epithelial cells due to inflammatory processes in the intermediate space between the tubules (interstitial nephritis). This result suggests that uMCP-1 could represent a useful biomarker for early detection of renal dysfunction. The lack of significant results with the uKIM-1 biomarker may be attributableto the absenceof renal injury of ischemic origin due to the importantreduction in thrombotic events following